P112 Speech And Language Therapy By Skype™ For Vocal Cord Dysfunction And Chronic Cough. (10th November 2014) - Lillie, SF; Haines, J; Vyas, A; Fowler, SJ
Abstract : Introduction: The Airways Service at Royal Preston Hospital receives tertiary referrals from across the UK. When a diagnosis of vocal cord dysfunction (VCD) or chronic cough is made and speech and language therapy (SLT) required, patients undergo weekly therapy (minimum four sessions), which some may struggle to attend due to pre-existing commitments and/or travel time. As SLT typically does not require 'hands-on' therapy we felt that Skype™ videoconferencing may be a useful mode of treatment delivery. We present our initial experience of this service. Methods: A six-month pilot was completed whereby patients were offered SLT over Skype. Prior to therapy all patients were seen by the respiratory consultant and speech and language therapist for assessment and flexible laryngoscopy. Patients required confidential webcam access and proficiency. Symptom questionnaires were completed pre and post therapy (for VCD the 12 item VCDQ; for chronic cough the 19-item LCQ), and patient satisfaction questionnaires and flexible laryngoscopy performed post therapy. Results: Eleven people have completed SLT over Skype™ to date, and all demonstrated improvement in symptoms following therapy. Patients with VCD showed a decrease in score on the VCDQ from median (range) 48 (12–53) pre therapy to 40 (7–42) post therapy [minimal clinical important difference (MCID) 5]. Patients with chronic cough showed an increase on the LCQ from median (range) 6.4 (4.6–8.2) pre therapy to 12.2 (10–14.6) post therapy (MCID 1.3). Improvements in laryngeal tension and sensitivity were noted in all cases. All patients gave positive feedback in their patient satisfaction questionnaire scoring "very satisfied" or greater. On three occasions Skype connection problems delayed sessions by a few days. Conclusions: Virtual consultations provide the opportunity to treat patients in a more time efficient and practical way, and improvements in patient-reported symptoms and laryngeal appearances were similar to those of patients attending therapy sessions in chest clinic. This data gives support to pursue formalised tariffs for a specialised telehealth service. We feel that Skype should continue as a regular therapy option for patients and other members of the multi-disciplinary team (MDT) should consider this method of therapy delivery.